Mobilities and Utopias: a critical reorientation. Issue 1 (2nd January 2020) - López-Galviz, Carlos; Büscher, Monika; Freudendal-Pedersen, Malene
ABSTRACT: What does utopian thinking have to offer students and scholars of mobility? Could 'mobile utopias' assist us in envisioning futures – including those of mobility – differently? Do utopias provide a unique opportunity to examine the relationship between mobile societies and lives and the environments against which these are formed? By providing different ways of reading and arguing within different theoretical frameworks and doing so in relation to the contexts their contributions engage, the articles included in this special issue explore the limits of what the mobile utopias of the future might be, their social and spatial dimensions, and their totalizing, fragmentary, or, personal definitions. As a whole, the issue contributes to the intellectual project of how to turn utopia into a method, as Levitas, Jameson, Harvey, and others have long encouraged us to do. With a few exceptions, utopias have not received the attention they deserve from mobilities scholars. Our aim in putting together this special issue is to redress this balance and invite further reflection on what utopian thinking might offer current debates in mobilities scholarship. This Introduction draws connections across approaches, foci, methods, geographies, and sources, including those deployed in the issue's six articles, in the interest of excavating possible hopeful orientations through critique. Central to this is the recognition of the significance of critiquing the images of mobility which circulate widely (think of drones) and of the necessity to listen attentively to voices overlooked by mobility futures which stand far removed from the reactions and feelings of people in their everyday worlds. Ours is an invitation both to pay close attention to what utopian thinking does – rather than what utopia is – and to help us carve out a new intellectual space where to reflect on the how, when and where mobilities and utopias meet, now, but also in the past, and in the future.